Resilience Optimization for Medical Device Distribution Networks Based on Node Failures - Xiao, Jianhua; Wang, Fei (International Journal of Supply Chain Management, 2014)
The Location of distribution centers for medical device is concerned with how to select distribution centers from a potential set so that the total cost is minimized and the resilience is maximized. In the paper, an optimization model for a resilient medical devices distribution networks is proposed based on node failure probability, node failure costs and other factors. Furthermore, the validity and feasibility of the model is explained with an example